2019
DOI: 10.1136/jnnp-2019-321496
|View full text |Cite
|
Sign up to set email alerts
|

Original research: Second IVIg course in Guillain-Barré syndrome with poor prognosis: the non-randomised ISID study

Abstract: ObjectiveTo compare disease course in patients with Guillain-Barré syndrome (GBS) with a poor prognosis who were treated with one or with two intravenous immunoglobulin (IVIg) courses.MethodsFrom the International GBS Outcome Study, we selected patients whose modified Erasmus GBS Outcome Score at week 1 predicted a poor prognosis. We compared those treated with one IVIg course to those treated with two IVIg courses. The primary endpoint, the GBS disability scale at 4 weeks, was assessed with multivariable ordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 25 publications
(32 reference statements)
1
21
0
Order By: Relevance
“…Some patients may nonetheless continue to deteriorate or experience fluctuations of symptoms after the initial dose, necessitating the consideration of a second course of IVIg administration ( Hughes et al, 2007 ; Verboon et al, 2017 ). The benefit of a second course of IVIg has yet to be corroborated ( Walgaard et al, 2018 ; Verboon et al, 2020 ), although a minor increase in the serum IgG level was proposed as a predictor for poor outcomes after a single dose of IVIg ( Kuitwaard et al, 2009 ). IVIg is correlated with adverse events including stroke, hemolytic anemia, transfusion-related acute lung injury (TRALI), aseptic meningitis, and venous embolism ( Koichihara et al, 2008 ; Nguyen et al, 2014 ; Stetefeld et al, 2014 ; Baudel et al, 2020 ) ( Table 2 ).…”
Section: Canonical and Emerging Immunotherapies Of Guillain–barré Syndromementioning
confidence: 99%
“…Some patients may nonetheless continue to deteriorate or experience fluctuations of symptoms after the initial dose, necessitating the consideration of a second course of IVIg administration ( Hughes et al, 2007 ; Verboon et al, 2017 ). The benefit of a second course of IVIg has yet to be corroborated ( Walgaard et al, 2018 ; Verboon et al, 2020 ), although a minor increase in the serum IgG level was proposed as a predictor for poor outcomes after a single dose of IVIg ( Kuitwaard et al, 2009 ). IVIg is correlated with adverse events including stroke, hemolytic anemia, transfusion-related acute lung injury (TRALI), aseptic meningitis, and venous embolism ( Koichihara et al, 2008 ; Nguyen et al, 2014 ; Stetefeld et al, 2014 ; Baudel et al, 2020 ) ( Table 2 ).…”
Section: Canonical and Emerging Immunotherapies Of Guillain–barré Syndromementioning
confidence: 99%
“…43 The same results were also previously reported by an observational study by Verboon et al which showed that second IVIG doses could not significantly enhance the prognosis of poor GBS. 44 Although previous investigations have approached the efficacy of some other management modalities, none of these approaches have been proven to be significantly efficacious as compared to plasma exchange and IVIG. 45…”
Section: Managementmentioning
confidence: 99%
“…Complications from a second immunoglobulin course were not reported in the Verboon and colleagues’ study, but risks from venous and arterial thrombosis are likely to be greater with higher doses of IVIg. The definitive answer to the question of the efficacy of a second immunoglobulin dose for GBS will have to await the results of the randomised controlled trial recently completed in the Netherlands 17…”
Section: This Editorial Comments On a Large Prospective Study Of Gbs mentioning
confidence: 99%